Analisis Dissolved Gas Analysis Dan Klasifikasi Tipe Fault Pada Minyak Trafo Dengan Metode Naive Bayes Classifier Pada Transformator Daya 150 kV - Ariyani, Sofia (Jurnal Teknik Elektro dan Komputasi (ELKOM), 2019)
Transformers are very important in electric power systems as well as in industry, therefore preventive maintenance is very necessary. One such treatment is the treatment of transformer oil. DGA (is an analysis of dissolved gas in transformer insulation oil and is one form of treatment for transformer insulation oil). In this final project, we will discuss how to analyze transformer oil data from DGA test and fault type classification using the naive bayes classifier method. The data from the transformer oil test with the DGA will later be classified which are then analyzed using Naive Bayes classifier and calculate the evaluation results with precision, recall, accuracy.Data SDYhttps://materassomemory.org/https://visualresearchnetwork.org/https://brazoriafumc.org/https://atmamayor.com/https://viralblasts.com/Bloom ScapeRokokbetRokokbetScatter HitamRokokbethttps://press.umam.edu.my/Rokokbethttps://theusajournals.com/RokokbetShiowlaRokokbetRokokbetRokokbetRokokbetRokokbetShiowla